Abstract 10382: Large Lipid-Rich Plaque Predicts Intra-Stent Thrombus Formation After Primary Pci in Patients with Acute Coronary Syndrome: Insights from Near-infrared Spectroscopy and Optical Coherence Tomography Imaging Analysis - Kitahara, Satoshi; Kataoka, Yu; Murai, Kota; Iwai, Takamasa; Sawada, Kenichiro; Matama, Hideo; Honda, Satoshi; Fujino, Masashi; Yoneda, Shuichi; Takagi, Kensuke; Otsuka, Fumiyuki; Asaumi, Yasuhide; et al. (Circulation (New York, N.Y.), 2021)
BackgroundsThe formation of intrastent thrombus is a PCI-related complication in subjects with ACS, which infrequently causes acute stent thrombosis. Given that lipid-rich plaque, a substrate for ACS, activates inflammation inducing prothrombotic state, the degree of lipidic plaque materials may associate with intrastent thrombus formation. MethodsCulprit lesions in 70 ACS subjects (=STEMI/NSTEMI/uAP=28/27/15) receiving newer-generation DES implantation were evaluated by both near-infrared spectroscopy (NIRS) and optical coherence tomography (OCT) imaging. NIRS-derived 4-mm maximum lipid-core-burden index (maxLCBI4mm) at culprit lesion was measured prior to PCI. OCT-derived intrastent thrombus-burden index (ITBI) after stent implantation were calculated as follows[Σ(every 1-mm cross sectional thrombus-arc score1=1-90°,2=91-180°,3=181-270°,4=271-360°)/analyzed length]x(averaged longitudinal length). ITBI was compared between subjects with maxLCBI4mm<400 and ≥400. ResultThe averaged maxLCBI4mm was 525±236, and dual-antiplatelet therapy with aspirin and clopidogrel, and aspirin and prasugrel was used in 43 and 56%, respectively. On OCT imaging analysis, maxLCBI4mm was significantly associated with ITBI (r=0.55, p<0.001, Figure), whereas there were no significant relationships of minimum stent area (MSA) (r=0.18, p=0.13) and stent malapposition diameter with ITBI (r=0.00. p=0.97). Multivariate analysis demonstrated maxLCBI4mm as an independent predictor of higher ITBI even after adjusting MSA, stent malapposition and other clinical characteristics (Table). ConclusionsThe presence of lipid-rich plaque was associated with intrastent thrombus formation in the setting of ACS. Our findings suggest the potential importance to modulate activated prothrombotic cascade by using more potent antiplatelet agent in ACS patients exhibiting lipid-rich plaques.